UPAYA MENINGKATKAN PEMAHAMAN DAN KEAMANAN DALAM PENGGUNAAN APLIKASI BRIMO KEPADA NASABAH DI PT BANK RAKYAT INDONESIA (BRI) DI KANTOR KCP AHMAD YANI - Sihotang, Lidia; Agustiawan (CV. Kalimasada Group, 2023)
Bank BRI launched the BRI Mobile Banking (Brimo) application with the aim of improving services to customers and making it easier for customers to make transactions. With the BRImo application, the mindset of customers and bank employees needs to be changed and adapted to using the mobile banking application. This dedication article aims to explain efforts to increase understanding and security in using the BRImo application for BRI Bank customers at the KCP Ahmad Yani Pekanbaru office. The method used is customer service, interviews and problem solving by the service team. By providing direct explanations to customers about the benefits, convenience and security of using the BRImo application, users can increase their trust in using the application.